Mediating Effect of Filial Piety Between the Elderly’s Family Resource Contribution and Their Family Power: Evidence from China - Liu, Xin; Bai, Shuying (Frontiers in Psychology, 2022)
With the development of rationalism, although the concept of filial piety is still an important factor affecting family relations, its rules have changed. Based on the resource theory and by measuring family power via the role played in family decision-making (FDM), this study explored the mediating role of filial piety norms between elderly’s family resource contributions and family power in intergenerational cohabitation families in Mengzhou city, China. Using a stratified sampling method, 1,200 elderly people were recruited for data collection. Multiple linear regression analysis was used for testing. The results show that (1) the elderly still have some FDM in Chinese intergenerational cohabitation families, and the family power of elderly men is still higher than that of elderly women, which indicate that the influence of traditional patriarchal norms still exists in the family. (2) Filial piety culture mediates between the elderly’s relative economic income (relative to their adult children) and their family power and also mediates the relationship of the elderly’s relative educational level (relative to their adult children) and their family power. It shows that the resources of the elderly relative to their children affect the filial piety of their adult children and then affect the FDM of the elderly. The study is theoretically and practically meaningful.